A 10 bit interface circuit for an array of capacitive transducers - Vosoughi, Mohammad Ali. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Terahertz Cameras are going to be widely used in many places, speci cally for medical purpose and there are many advantages over the use of terahertz signals for imaging. Among di erent methods of terahertz imaging, the transformation of the THz signals into the form of absorbed heat and mechanical displacements can be used for medical purposes. The use of mechanical de ections for cameras requires a method for measuring the displacement. From di erent modalities for displacement sensing, capacitor based displacements are widely used in literature. For many reasons, including cost and feasibility with current technologies and compatibility with MEMS fabrications process, capacitive displacement transducers are the best choice for photo-mechanical cameras. Simulations show that the interface circuit should satisfy a su ciently good safe margin for operation of circuit in di erent sensing capacitor dimensions. A rail-to-rail voltage at the output of the sensor interface circuit might limit tolerance of the fabrication process. Therefore, conventional method with limited output voltage swing is employed to provide su ciently exible solution. A 10 bit data converter transduces the capacitance value to a digital modulated signal.
Keywords: Terahertz technology.